If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -5)(x + 3) = 0 Reorder the terms: (-5 + 7x)(x + 3) = 0 Reorder the terms: (-5 + 7x)(3 + x) = 0 Multiply (-5 + 7x) * (3 + x) (-5(3 + x) + 7x * (3 + x)) = 0 ((3 * -5 + x * -5) + 7x * (3 + x)) = 0 ((-15 + -5x) + 7x * (3 + x)) = 0 (-15 + -5x + (3 * 7x + x * 7x)) = 0 (-15 + -5x + (21x + 7x2)) = 0 Combine like terms: -5x + 21x = 16x (-15 + 16x + 7x2) = 0 Solving -15 + 16x + 7x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -1x)(5 + -7x) = 0Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(5 + -7x)' equal to zero and attempt to solve: Simplifying 5 + -7x = 0 Solving 5 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -7x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -7x = 0 + -5 -7x = 0 + -5 Combine like terms: 0 + -5 = -5 -7x = -5 Divide each side by '-7'. x = 0.7142857143 Simplifying x = 0.7142857143Solution
x = {-3, 0.7142857143}
| 3x+7=4x-1 | | -2(-2-n)= | | 4x^2+2=36 | | 21x^2-58x+21=0 | | 13-10x=143-45x | | 4(y-2)=52 | | 5x*4=305 | | (n+2)(4n-1)=0 | | 18x^2+15x+2=0 | | 2x+2=1x | | 8m-12/40= | | -5(p+2)=2(p-15)+p | | p=h | | p=9 | | 2x+4=2y | | 20-4=64 | | 42=48 | | 5m+14=7m-6 | | 10a^2+31a-14=0 | | 4x-20=30 | | 30p+48=0 | | 16-p=7 | | 5x-5=8x+7 | | -5(7n+1)= | | 13=5-8 | | (2x+6)=12 | | 5m-14=7m-6 | | 85c-0.05(2.00c)=T | | 16x^2+21x+25=0 | | (4x-4)(x+11)=0 | | (x+1).14= | | 3-4y+6=6y+1-5y |